Quo vadis DGPRÄC: associated members' goals for the future - Kolbenschlag, Jonas; Paprottka, Felix; Wagner, Juri; Goertz, Ole; Liebau, Jutta; Daigeler, Adrien; Horch, Raymund E.; Horch, Raymund E.; Lehnhardt, Marcus (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2017)
Plastic surgery is extremely diverse and offers various fields of work. To provide optimal support for plastic surgeons in training, it is therefore paramount to know their mid- and long-term goals. To that end, we conducted a web-based survey among the 462 associated members of the German Association of Plastic, Reconstructive and Aesthetic Surgeons (DGPRÄC). Besides asking questions about the current status, we specifically inquired about the pursued setting and main area of work. 84 completed questionnaires were evaluated. Most respondents saw their future in a private practice setting. Reconstructive surgery and aesthetic surgery were by far the most sought-after fields, while only a few of the associated members pursued a career in hand surgery, and none of them wished to work in burn care. At the same time, they felt that aesthetic surgery was the field where training was most insufficient. Therefore, measures need to be taken to improve the training in aesthetic surgery. Also, it is paramount to increase the attractiveness of both the fields of hand surgery and burn care to assure highly qualified care in the future.
EVALuna2:32839